Does Thrombocyte Size Give Us an Idea about Thrombocytosis Etiology? - Selami Kocak Toprak; Betul Erismis; Sema Karakus; Nazmiye Kursun; Aysegul Haberal; Mustafa Gurhan Ulusoy (The Scientific World Journal)
In the presence of a pathogenetic mutation in JAK2 or MPL, a differential diagnosis of essential thrombocythemia (ET) from reactive causes is relatively simple. However, in patients with suspected ET who lack JAK2 and MPL mutations, the exclusion of secondary causes is especially important. The study was aimed to explore the clinical application of particularly mean platelet volume (MPV), hemoglobin, red blood cell indices, white blood cell, serum iron profile, and C-reactive protein level in the differential diagnosis of thrombocytosis. Medical records of 49 patients, consisting of reactive thrombocytosis (RT) and ET were retrospectively reviewed. The mean MPV level in RT group was 7.49 fL, and in ET group was 8.80 fL (P<0.01). A cutoff point of <8.33 fL was found to have significant predictive value according to ROC curve analysis. This cutoff was associated with 83% positive predictive value (PPV) and 74% negative predictive value (NPV) in the diagnosis of ET and had a sensitivity of 65% and specificity of 89% for ET. Investigation of MPV is cheap, quick, and noninvasive, and may serve as a predictor of primary thrombocytosis. High sensitivity, specificity, PPV, and NPV enable this test an important tool and a possible surrogate marker in clinical practice.